2013
DOI: 10.1038/nm.3253
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of hepatic innate immunity by hepatitis C virus

Abstract: Hepatitis C virus (HCV) is a global public health problem involving chronic infection of the liver in over 170 million people. Chronic HCV causes liver disease and is linked with liver cancer. Viral innate immune evasion strategies and human genetic determinants underlie the transition of acute HCV infection to viral persistence and the support of chronic infection. Host genetic factors, such as sequence polymorphisms in IFNL3, a gene in the host interferon system, can influence both the outcome of infection a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
292
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 253 publications
(295 citation statements)
references
References 116 publications
2
292
0
1
Order By: Relevance
“…In addition, antiviral immunity triggered by exosomal transfer of viral RNA to pDCs has been suggested in HCV infection (3). HCV persistence and pathology, depends on strategies evolved to avoid innate recognition in infected cells (2). It will become important to resolve how pathogenic (viral) RNAs are incorporated and transported via exosomes, as the packaging machineries of virion capsids are presumably lacking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, antiviral immunity triggered by exosomal transfer of viral RNA to pDCs has been suggested in HCV infection (3). HCV persistence and pathology, depends on strategies evolved to avoid innate recognition in infected cells (2). It will become important to resolve how pathogenic (viral) RNAs are incorporated and transported via exosomes, as the packaging machineries of virion capsids are presumably lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Some RNA viruses establish a chronic productive infection: for example, hepatitis C virus (HCV), which evolved strategies to escape from innate immune sensors contributing to its pathophysiology (2). Nevertheless HCV, an enveloped RNA virus, can be recognized by sensory plasmacytoid dendritic cells (pDCs) (3).…”
mentioning
confidence: 99%
“…Infected cells also use different cellular surveillance mechanisms to block virus replication and spread 6. One such mechanism involves the production of IFN, which directly inhibits virus replication 7. The other mechanism involves blocking the spread of infection by inducing p53‐mediated cellular apoptosis 8…”
Section: Introductionmentioning
confidence: 99%
“…Over the past several years, many investigators, including our own, showed that HCV‐associated ER stress induced an autophagy response, which results in impaired host innate immunity through blocking endogenous IFN production7, 9 and also escapes from exogenously added IFN‐α and ribavirin (RBV)‐based antiviral therapy through degradation of interferon‐alpha receptor 1 and RBV transporter 10, 11. In this report, we found that HCV infection induces chaperone‐mediated autophagy (CMA) as a cell survival mechanism to avoid the ER‐stress response.…”
Section: Introductionmentioning
confidence: 99%
“…The two key cellular sensors are Toll-like receptor 3 (TLR3), which senses doublestranded RNA (dsRNA) within endosomes, and the RNA helicase retinoic acid-inducible gene I (RIG-I), which senses intracellular double-stranded RNA or single-stranded viral RNA (Wang et al, 2009;Green et al, 2012Green et al, , 2014Li et al, 2012;Horner and Gale, 2013). Signaling initiated by TLR3 and RIG-I is transmitted through the adaptor proteins Toll/IL-1 receptor domain-containing adaptor inducing IFN-beta (TRIF) and mitochondrial antiviral-signaling protein (MAVS) respectively, to interact with TNF receptor-associated factor 3 (TRAF3) and converge on the transcription factors, interferon regulatory factor 3 (IRF3) and NF-κB.…”
Section: Introductionmentioning
confidence: 99%